Inhibition of Store-Operated Calcium Entry Attenuates MPP+-Induced Oxidative Stress via Preservation of Mitochondrial Function in PC12 Cells: Involvement of Homer1a - Li, Xia; Chen, Wei; Zhang, Lei; Liu, Wen-bo; Fei, Zhou (PLOS ONE, 2013)
The process of store-operated calcium entry (SOCE), whereby the release of intracellular Ca2+ from endoplasmic reticulum (ER) activates Ca2+ influx channels in the plasma membrane, has been demonstrated to impact a diverse range of cell functions. In the present study, we investigated the potential protective effect of SOCE inhibition against 1-methyl-4-phenylpyridinium (MPP+) injury by using pharmacological antagonists or specific small interfering RNA (siRNA) in PC12 cells. The results showed that both antagonists (15 μM MRS-1845 and 50 μM ML-9) and stromal interacting molecule-1 (STIM1) targeted siRNA (Si-STIM1) significantly increased cell viability, decreased apoptotic cell death and reduced intracellular reactive oxygen species (ROS) production and lipid peroxidation in MPP+ injured PC12 cells. SOCE inhibition also prevented MPP+ induced mitochondrial dysfunction and activation of mitochondrial related apoptotic factors, while had no effect on mitochondrial biogenesis. Moreover, inhibition of SOCE by antagonists and siRNA increased the expression levels of Homer1a mRNA and protein, and knockdown of Homer1a expression by specific siRNA partly reversed the protective effects induced by SOCE inhibition in PC12 cells. All these results indicated that SOCE inhibition protected PC12 cells against MPP+ insult through upregulation of Homer1a expression, and SOCE might be an ideal target for investigating therapeutic strategy against neuronal injury in PD patients.